2016
DOI: 10.1016/j.mam.2016.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of oxidized proteins by the proteasome: Distinguishing between the 20S, 26S, and immunoproteasome proteolytic pathways

Abstract: The proteasome is a ubiquitous and highly plastic multi-subunit protease with multi-catalytic activity that is conserved in all eukaryotes. The most widely known function of the proteasome is protein degradation through the 26S ubiquitin-proteasome system, responsible for the vast majority of protein degradation during homeostasis. However, the proteasome also plays an important role in adaptive immune responses and adaptation to oxidative stress. The unbound 20S proteasome, the core common to all proteasome c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
165
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(173 citation statements)
references
References 166 publications
(228 reference statements)
3
165
0
5
Order By: Relevance
“…As the focus of this minireview is on recent insights, these proteolytic pathways will only be briefly reviewed and more detailed reviews can be found elsewhere (Pickering and Davies, 2012;Settembre et al, 2013;Chondrogianni et al, 2014;Raynes et al, 2016). Natively folded proteins can be efficiently reversed by enzymes such as thioltransferases and methionine sulfoxide reductases.…”
Section: Oxidised Protein Removal From the Cytoplasm Nucleus And Endmentioning
confidence: 99%
“…As the focus of this minireview is on recent insights, these proteolytic pathways will only be briefly reviewed and more detailed reviews can be found elsewhere (Pickering and Davies, 2012;Settembre et al, 2013;Chondrogianni et al, 2014;Raynes et al, 2016). Natively folded proteins can be efficiently reversed by enzymes such as thioltransferases and methionine sulfoxide reductases.…”
Section: Oxidised Protein Removal From the Cytoplasm Nucleus And Endmentioning
confidence: 99%
“…Однако в последнее время гипотеза о том, что протеасомы в клетке существуют в основном в виде 20S-комплексов и во многих случаях играют решающую роль в убиквитин-независимой деградации белков (например, в условиях окислительного стресса, при старении и развитии ряда сердечно-сосудистых и нейродегенеративных заболеваний) [31], получает всё большее подтверждение.…”
Section: структурные предпосылки убиквитин-независимой деградации белunclassified
“…Деградации непосредственно 20S протеасомой подвергаются белки, содержащие неструктурированные области, появившиеся в результате окисления, мутации или старения [27][28][29][30][31][32]. Подобное расщепление характерно и для так называемых внутренне неупорядоченных белков, то есть нативных белков, содержащих неупорядоченные участки (partly-folded proteins) [33] (44)убиквитин-независимое расщепление.…”
Section: структурные предпосылки убиквитин-независимой деградации белunclassified
See 1 more Smart Citation
“…7 Immunoproteasome is also important for the generation of peptides for antigen presentation; moreover, recent studies also suggest a pleiotropic role in cellular function of the immunoproteasome. [8][9][10] There is an amounting body of research on the small-molecule inhibitors of proteasomes. 5,11 Both marketed medicines, bortezomib and carfilzomib, equally inhibit the catalytically active β5 subunits of the constitutive proteasome and the immunoproteasome.…”
Section: Introductionmentioning
confidence: 99%